Study on the Potential of Environmentally Friendly Fire Bricks Based on Local Waste Materials Using Ceramic Powder, Glass Powder, and Rubber Ash - Resmaindra, Muhammad Thariq; Putri, Cintri Anjani Rahmada; Arissaputra, Sofian (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2026)
Fire bricks are construction materials commonly used as liners in structures exposed to high temperatures, such as furnaces and boilers. Conventional fire brick production requires high energy consumption and generates significant carbon emissions. This study aims to develop eco-friendly fire bricks by utilizing industrial waste materials such as rubber ash, glass powder, and ceramic waste, combined with kaolin, alumina, and bentonite as binding and strengthening agents. The research was conducted experimentally in the laboratory with five composition variations (S1–S5). Each sample was molded, cured for seven days, and then fired gradually up to 1250°C. Tests were performed to evaluate density, compressive strength, and thermal resistance. The results showed that the composition of alternative materials significantly affected the physical and mechanical properties of the fire bricks. The highest density was obtained in variation S2 at 2604.48 kg/m³, with a maximum compressive strength of 15.26 MPa. Increasing the proportion of substitution materials led to a decrease in density and compressive strength due to higher porosity formation. All variations met the minimum refractory temperature resistance standards, with compositions containing refractory cement and ceramic waste demonstrating the best thermal stability. This study indicates that incorporating industrial waste materials as partial substitutes in fire brick production can reduce environmental impact while producing materials that are technically and economically efficient. Keywords: fire brick, alternative materials, industrial waste, compressive strength, thermal resistance